Керамічні комплекси третьої чверті XV ст. замку Фуна: начиння «гарнізонної кухні» - Тесленко, І.Б. (Археологія і давня історія України, 2020)
Замок Фуна — одна з найяскравіших пам’яток фортифікаційної архітектури середньовічного Криму. Нині в деталях осягнуто етапи будівельної історії фортеці та запропоновано реконструкцію її зовнішнього вигляду. Однак чимало проблем, що стосуються повсякденного життя будівельників, захисників та інших мешканців фортеці, ще потребують вивчення. З-поміж них — аналіз керамічних комплексів, що добре збереглися і датуються вузько. Тут подамо кераміку, що походить з так зв. гарнізонної кухні. The Funa fortress is located in southern Crimea and is one of the reference architectural and archaeological complexes of the Northern Pontic Region with precise date of existence. The fortress was built by Mangup authorities near 1423 on the border with possessions of Genoese and was destroyed in a fire during the Turkish invasion of the Crimea in 1475. The detailed chronology of the site which includes three stages of its construction history — 1423, 1425—1450s and 1459—1475, has been developed so far. So it becomes possible to clarify the dating of ceramic finds in line with these periods also. Ceramic assemblages of the last stage from the layers of fire and destruction of 1475 are the most representative. There is the complex from courtyard 1 among them.